UJI BERBAGAI HERBISIDA DALAM MENGENDALIKAN GULMA PADA PERTANAMAN PADI SAWAH TEBAR LANGSUNG DAN KEDELAI DI LAHAN BASAH - Anwar, Risvan (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2010)
The purpose of the research was to know effect some kind herbicides to control the weeds paddy direct seeded and soybean in wet areal. A randomized block design was used 3 replications and 8 treatments namely: (A) Agristar; (B) Ally Plus; (C) DMA; (D) Metafuron; (E) Agristar and DMA 6; (F) Agristar and Metafuron; (G) Ally Plus and DMA 6; (H) Ally Plus and Metafuron. The result suggested that just pre plant herbicides (Ally Plus and Agristar) or post emergence herbicides (DMA 6 and Metafuron) only was not effective to control the weeds paddy direct seeded and soybean in wet areal. Pre plant herbicide (Ally Plus) that next is followed post emergence DMA 6 most effective to control the weed paddy direct seeded and soybean in wet areal.